2008
DOI: 10.1016/j.freeradbiomed.2008.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of Nox1 and Nox4 in basal and angiotensin II-stimulated superoxide and hydrogen peroxide production

Abstract: NADPH oxidases are major sources of superoxide (O2∸) and hydrogen peroxide (H2O2) in vascular cells. Production of these reactive oxygen species (ROS) is essential for cell proliferation and differentiation, while ROS overproduction has been implicated in hypertension and atherosclerosis. It is known that the heme-containing catalytic subunits Nox1 and Nox4 are responsible for oxygen reduction in vascular smooth muscle cells from large arteries. However, the exact mechanism of ROS production by NADPH oxidases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
262
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(283 citation statements)
references
References 58 publications
15
262
5
1
Order By: Relevance
“…To assess the role of scaffolding protein EBP50 in Nox1 activation, O 2 •-production was investigated in aortic VSMC from EBP50 KO vs. WT mice. It is well established that 100 nM AngII treatment significantly increases O 2 •-levels, and this increase is Nox1-derived (20)(21)(22)(23)(24)(25)(26). We corroborated these findings using concentration and time response experiments and by showing that siRNA against Nox1 abolished the signal (Fig.…”
Section: Angiisupporting
confidence: 83%
“…To assess the role of scaffolding protein EBP50 in Nox1 activation, O 2 •-production was investigated in aortic VSMC from EBP50 KO vs. WT mice. It is well established that 100 nM AngII treatment significantly increases O 2 •-levels, and this increase is Nox1-derived (20)(21)(22)(23)(24)(25)(26). We corroborated these findings using concentration and time response experiments and by showing that siRNA against Nox1 abolished the signal (Fig.…”
Section: Angiisupporting
confidence: 83%
“…Second, several recent independent reports indicate that Nox4 generates predominantly H 2 O 2 (as further confirmed in the current study) whereas Nox2 primarily generates O 2 − (refs. [17][18][19][20]. These differences in regulation, activation mechanism, subcellular location, and ROS generation translate into isoform-specific actions in isolated cellular models (9,19,22,33).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20]. These differences in regulation, activation mechanism, subcellular location, and ROS generation translate into isoform-specific actions in isolated cellular models (9,19,22,33). In the heart, previous studies in mouse models of defective Nox2 activation or its deletion showed that Nox2 is detrimental during remodeling, causing increased hypertrophy, apoptosis, and contractile dysfunction (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of ROS production (superoxide, peroxynitrite, and other downstream single-electron reactive-oxygen intermediates) was accomplished by exposing the stimulated cells to either 50 mol/L cellpermeable CMH (1-hydroxy-3-methoxy-carbonyl-2,2,5,5-tetramethylpyrrolidine) or 50 mol/L cell-impermeable PPH (1-hydroxy-4-phosphono-oxy-2,2,6,6-tetramethylpiperidine) spin probes (Noxygen Science Transfer & Diagnostics GmbH, Elzach, Germany) and analyzed using a table-top EPR spectrometer (eScan; Bruker BioSpin, Billerica, MA). [31][32][33] Various amounts (in micromoles per liter) of CM radical were measured to generate a standard curve to quantify the amount of oxidants produced by wild-type and EC-SOD KO cells. EPR settings were as follows: field sweep, 50 G; microwave frequency, 9.78 GHz; microwave power 20 mW, modulation amplitude, 2 G; conversion time, 327 ms; time constant, 655 ms; and receiver gain, 1 ϫ 10 5 .…”
Section: Immunolabeling and Western Blot Analysismentioning
confidence: 99%